Progress and perspectives of self-powered gas sensors - Lei Wang; Xinqi Yao; Yin Zhang; Gaoqiao Luo; Bo Wang; Xinhai Yu (Next Materials, 2024)
Ambient gas monitoring has been studied for over a century, and the field of self-powered gas sensors is advancing rapidly. Currently, the main solution is the conversion of ambient energy into electrical energy and its use to power gas sensors. Various energy harvesters are available, such as frictional electric nanogenerators, piezoelectric nanogenerators, thermoelectric generators, and photovoltaic cells, to capture different forms of energy. Simultaneously, energy harvesters can be designed to power gas sensors for different atmospheric sensing requirements. Self-powered gas sensors have shown great promise in applications such as human health monitoring, the detection of hazardous gas leaks, the prevention of drunk driving, the preservation of food and pharmaceuticals, agricultural production, and the monitoring of the condition of industrial equipment. However, for commercial applications, significant progress still needs to be made on self-powered gas sensors. In this review, an objective overview of four typical energy harvesting devices is provided, covering types, structures, materials, and energy sources. Self-powered gas sensors are systematically categorized, with the latest research progress in this field presented. Future trends in self-powered gas sensing are then envisioned and the potential for commercialisation is discussed.